Manufacturers and retailers in the global economy - Horst Raff; Nicolas Schmitt (Kiel Institute for the World Economy (IfW), 2011)
We develop a general-equilibrium model to capture key features of the retailing and of the manufacturing industry in order to understand how these two industries interact and how labor is allocated between them. We show that the observed shift in employment from manufacturing to retailing, the rise in retailer product assortment and the emergence of slotting allowances in many retail markets are consistent with the global integration of product markets, while higher retail market concentration is best explained by technological change in retailing. We also identify a novel benefit from market integration consisting of efficiency gains in the vertical distribution chain.
Keywords: F12; F15; L13; 330; Classification: international trade; product variety; retailing; slotting allowance; multi-product firm; Einzelhandel; Verarbeitendes Gewerbe; Lieferanten-Kunden-Beziehung; Sektorale Beschäftigungsstruktur; Globalisierung; Produktdifferenzierung; Mehrproduktproduktion; Wirtschaftskonzentration; Allgemeines Gleichgewicht; Theorie